Glossário terminológico da inteligência emocional - Aranda, Cristiane de Melo (2010)
The present dissertation, ruled on Language Science, has the aim of systematizing the nomenclature of Emotional Intelligence, a subfield in constitution in the area of Psychology. The final result is presented in the form of the Terminological Glossary of Emotional Intelligence, whose elaboration respected the epistemological foundations and methodological procedures of the Communicative Theory of Terminology (CTT). The choice of the theme considered the increasing interest of researchers of different areas in the reinsertion of emotions in the focus of the scientific works, mainly in the scope of Social Psychology, as well as its recurrent interdisciplinarity with the Neuropsychology and Psychometria. The research is structured in 10 important technical texts, among books, dissertations and scientific articles which compose the corpus from which 133 terms were elicited. Due to these characteristics, the work is inserted in the non-exhaustive modality, and also, as from Corpus Linguistics, can be described as contemporary, of sampling, specialized, monolingual, non labeled and non documented. As far as the terms are concerned, they are presented in alphabetical order, according to eight subfields identified by the Conceptual Map, they are: 1) Psychology and Emotions; 2) Affective States; 3) Emotional Intelligence as Zeitgeist; 4) Emotional Intelligence as Personality; 5) Emotional Intelligence as Mental Ability; 6) Psychometria and Emotional Intelligence; 7) Neuropsychology and Emotional Intelligence; 8) Emotional Intelligence and Related Ideas. As tools of terminographic work, it was used the software Unitex version 2.0 for extracting the terms, the Microsoft Access for elaboration of the terminological cards and the Microsoft Excell for organizing the definitional data base. Lastly, considering its technical feature, this glossary is directed to specialized readers, from the thematic field of Emotional Intelligence, as well as from the technical field of Terminology. It can also arise interest of the general public.